Online Learning and Students’ Performance in Uganda Christian University Arua Campus as a Higher Institution of Learning - Joshua Omona Otim (Uganda Christian University, 2025)
This study investigated online learning and students’ performance in Uganda Christian University Arua Campus. Solemnly subjective to the studies objectives, key to note is; to determine the influence of online learning on student, to examine the academic performance of students using predominantly online learning and to ascertain the relationship of online learning and students’ performance in higher institutions of learning such as UCU. The study employed both descriptive survey and correlation analysis designs; data was obtained from 74 (98.6%) respondents through questionnaires. The research showed that the influence of online learning on students’ academic performance in regards to students’ participation 3.42(68.4%), delivery of lectures 4.14(82.4%) and flexibility and access 4.09(81.8%) was high as indicated by the grand mean 3.88 (77.6%) and standard deviation .89 to students’ performance. Further explorations were made examining academic performance as far as online learning is concerned looking at academic excellence, learning style and self-motivation. The findings aimed to inform educators, and Uganda Christian University, its campuses and policymakers to develop strategies to mitigate the potential challenges of using online learning as revealed by the correlation analysis. The researcher used descriptive survey design in the study. Descriptive design employing qualitative research technique which provides full description of attitude of respondents. More so qualitative research technique was used for numerical information. Validity was under a guided and guarded approval of the tool used by the academic supervisor. Summative, the research investigated the influence of online learning on students’ performance with a conclusion that online learning has an extreme influence on students’ academic performance. In a commendation the researcher recommended finding more efficient strategies to increase student participation in online learning settings, Change in learning, lecture delivery methods to combat the challenges encountered during online learning.
Undergraduate